Intraluminal stone in a PD catheter : third world case - Béatrice Champtiaux Dechamp; Lise Mandart; Pierre-Yves Durand (RDPLF, 2018)
Only 2 cases of intraluminal peritoneal catheter lithiasis have been reported so far. A woman (68 years of age) on CAPD was admitted to hospital because of intermittent outflow obstruction of her peritoneal catheter. A stone was found in the catheter lumen. Its biochemical composition was the same as that of the 2 other cases previously described: calcium-hydroxycardonate-phosphate with an admixture of protein. The stone could not migrate through the intraperitoneal tip hole of the catheter because its size (3 x 4 mm) was greater than the catheter lumen (2.7 mm). That suggests in situ development, directly in the catheter lumen despite inflow-outflow dialysate daily regular rinsings. In the 3 cases, dialysate contained lactate and 1.75 mmol/L calcium.